2019
DOI: 10.7717/peerj.8175
|View full text |Cite
|
Sign up to set email alerts
|

The accumulation of Mn and Cu in the morphological parts of Solidago canadensis under different soil conditions

Abstract: Solidago canadensis L. is a drought-tolerant, invasive plant, characterized by a large biomass of underground and aboveground parts. The aim of this study was to assess the accumulation of manganese (Mn) and copper (Cu) in the roots and rhizomes and the stems, leaves, and inflorescence parts in S. canadensis from two locations that differed in soil pH, organic carbon, and Mn and Cu concentrations. The concentration of the metals in the samples was determined by the AAS method; the pH was determined by the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…It has also been proposed to be used as a rotation crop as a means of containing noxious weeds in an organic agriculture context [35]. Solidago spp., including S. virgaurea, have been claimed to have potential utility for phytoremediation purposes, based on their ability to transfer iron from soil to plants near iron processing industrial sites [35]; however, studies on other oligo-elements (such as zinc) have not identified particular hyperaccumulator properties for the plant [52], and whereas a number of papers have been published on the phytoremediation potential of S. canadensis [53,54], we could find none on S. virgaurea. The pollen of the latter is of good quality, and its availability may contribute to long-lived bees being able to survive a hard winter [55].…”
Section: Other Usesmentioning
confidence: 60%
“…It has also been proposed to be used as a rotation crop as a means of containing noxious weeds in an organic agriculture context [35]. Solidago spp., including S. virgaurea, have been claimed to have potential utility for phytoremediation purposes, based on their ability to transfer iron from soil to plants near iron processing industrial sites [35]; however, studies on other oligo-elements (such as zinc) have not identified particular hyperaccumulator properties for the plant [52], and whereas a number of papers have been published on the phytoremediation potential of S. canadensis [53,54], we could find none on S. virgaurea. The pollen of the latter is of good quality, and its availability may contribute to long-lived bees being able to survive a hard winter [55].…”
Section: Other Usesmentioning
confidence: 60%
“…It has also been proposed to be used as a rotation crop as a means of containing noxious weeds in an organic agriculture context [35]. Solidago spp., including S. virgaurea, have been claimed to have potential utility for phytoremediation purposes, based on their ability to transfer iron from soil to plants near iron processing industrial sites [35]; however, studies on other oligo-elements (such as zinc) have not identified particular hyperaccumulator properties for the plant [52], and whereas a number of papers have been published on the phytoremediation potential of S. canadensis [53,54], we could find none on S. virgaurea. The pollen of the latter is of good quality, and its availability may contribute to long-lived bees, able to survive a hard winter [55].…”
Section: Other Usesmentioning
confidence: 60%
“…Extracts of S. virgaurea contain C6-C1 glycosides (virgaureoside, leiocarposide) and aglycones (vanillic acid, gallic acid) [4,9,[56][57][58], C6-C3 polyphenolic acids (caffeic, chlorogenic, ferulic, synapic, 3-hydroxyphenylacetic acid, 3,4-dihydroxyphenylacetic, homovanilic, acids) [3,9,10,45,[53][54][55][56][57], a number of flavonoid molecules (mostly quercetin and kaempferol glycosides, as well as the free aglycons and small amounts of cyanidin derivatives) [3,4,9,45,49,59,60,[63][64][65][66][67], oleanane-type triterpene saponins [9,[68][69][70][71][72][73][74][75], essential oils containing and monoterpenes (alpha-and beta-pinene, myrcene, limonene, sabinene) [35,[76][77][78][79] and sesquiterpenes (germacrene D β-caryophyllene, α-humulene,), clerodane-type diterpenes [80], polysaccharides [81], and polyacetylenes [82] (tab. 1).…”
Section: Phytochemistrymentioning
confidence: 99%
“…The high tolerance of S. canadensis to soil contaminated with heavy metals and the accumulation of selected metals in the aboveground and underground parts of the plant can be used in the phytoremediation of contaminated soils. In polluted soils, the plant shows a particular tendency to accumulate Pb [Yang et al 2008;Xiang et al 2010;Antonijević et al 2012;Bielecka, Królak 2019a], Cd [Dąbrowska et al 2017], Hg [Tomiyasu et al 2005] and Cu [Antonijević et al 2012;Bielecka, Królak 2019b] in its underground parts. Research carried out in the vicinity of Olkusz, Poland (a region particularly contaminated with Pb and Zn), showed that S. canadensis accumulates, on average, 520 g Pb/ha (maximum about 3,500 g Pb/ha) and about 450 g Zn/ha (max.…”
Section: Positive Aspects Of the Presence Of Canadian Goldenrod In The Environmentmentioning
confidence: 99%
“…This is especially important in the case of goldenrod presence in landfills abundant in fine-grained fractions rich in heavy metals. The plant also has a tendency to transform some metals, such as Zn [Dąbrowska et al 2017;Bielecka, Królak 2019a] and Mn [Antonijević et al 2012;Bielecka, Królak 2019b], in its aboveground parts. For example, Canadian goldenrod in the Olkusz area accumulates, on average, about 470 g Zn/ha (max.…”
Section: Positive Aspects Of the Presence Of Canadian Goldenrod In The Environmentmentioning
confidence: 99%